Interleukin-4 Signaling Pathway and Effects in Allergic Diseases - Philips, N.; Samuel, P.; Samuel, M.; Perez, G.; Khundoker, R.; Alahmade, G. (Current Signal Transduction Therapy, 2018)
Background: Allergic diseases, such as atopic dermatitis and allergic asthma, are associated with increased inflammation and interleukin-4 (IL-4) signaling. An inhibitor of the IL-4 receptor, dupimulab, was approved recently for dermatitis. This goal of this review is to elucidate the mechanism and effects of IL-4 signaling. Methods: We reviewed information available in immunology and molecular biology textbooks, and research and review articles to accomplish our goal. Results: The increased inflammation, in allergic diseases, is due to inflammatory cytokines released from innate leukocytes and local tissue. The increased IL-4 signaling activates the helper Th2 cells to release IL-4, and the allergic effects. The IL-4 binds to its receptors to activate JAK1/JAK3 mediated nuclear translocation of the phosphorylated STAT6 dimer, which stimulates the expression of IgE antibodies in B-cells. The released IgE stimulates the release of histamines from mast cells, alters the expression of genes associated with fibrosis, and induces apoptosis of epidermal or epithelial cells. The resultant IL-4 effects in allergic diseases include pruritus or wheezing, fibrosis and/or altered expression of extracellular matrix proteins, and loss of epidermal or epithelial barrier function. Conclusion: The specific inhibition of the Il-4 signaling, through dupimulab that binds the IL-4 α receptor subunit, would be effective in the specific inhibition of the allergic response in patients with allergic dermatitis or asthma.
Keywords: STAT6